Implementasi Algoritma Base64 Untuk Verifikasi Qr Code Login Jaringan Wifi Berbasis Android - Abdul Hidayat; Pristiwanto Pristiwanto (Universitas Budi Darma, 2020)
In this day and age many people use the internet with wifi media because its use is easy and efficient, in contrast to the use of network cables because of its inefficient use and consuming a lot of space. But now the use of wifi is widely accessed by unauthorized people to access it and insecure login verification process and the amount of access that uses wifi on one SSID will result in a decrease in internet speed on wifi, to enter and verify it into a wifi network. text and numbers or security using the QR Code. Using a QR Code or an ordinary password will not be able to deal with people who are not entitled to such access, so it needs layered security to secure and verify wifi logins from people who are not entitled to access them. Base64 algorithm is one of the algorithms for encoding and decoding a data into an ASCII format, which is based on basic numbers 64 or can be referred to as one method used to encode binary data. In securing wifi by verifying the QR Code login wifi network using the base64 algorithm makes using wifi can be overcome and handled so that no one breaks into the wifi network because it can harm the users or owners of the wifi network